Robust quantum information processing with techniques from liquid-state NMR. - Jones, J (2003)
While nuclear-magnetic-resonance (NMR) techniques are unlikely to lead to a large-scale quantum computer, they are well suited to investigating basic phenomena and developing new techniques. Indeed, it is likely that many existing NMR techniques will find uses in quantum information processing. Here I describe how the composite-rotation (composite-pulse) method can be used to develop quantum logic gates which are robust against systematic errors.